(untitled) (Mathematical Proceedings of The Widya Mandira Catholic University, 2024)
The purpose of this research is to determine the of mathematical reasoning abilities in terms of learning independence in class VIII students at SMPK St. Maria Asumpta Kupang 2023/2024 academic year. This research is qualitative research with a descriptive approach. The subjects in this research were three students, consisting of 1 female student with high learning independence, 1 student with moderate learning independence and 1 female student with low learning independence. Data collection was carried out using several methods, including questionnaires, reasoning ability tests, and interviews. The data analysis technique used in this research consists of three stages, namely data reduction which is carried out by first focusing on important data. Then the presentation of the data is presented in descriptive-analytical text, and conclusions are drawn by explaining it descriptively. The results of this research show that the mathematical reasoning abilities of students with a high level of learning independence fulfill the four indicators of mathematical reasoning. The mathematical reasoning ability of students with a moderate level of learning independence doesn’t fulfill one indicator of the Mathematical reasoning indicators. The mathematical reasoning abilities of students with a low level of learning independence are not able to meet the mathematical reasoning indicators